Transitioning from undergraduate to postgraduate studies : A multistage evaluation of a discipline-specific writing intervention - Drennan, Laura Maria (Journal for Language Teaching, 2022)
This study attempted to address academics’ general concern about the steady decline in students’ academic writing abilities and the impact this has on students’ ability to demonstrate their learning and negotiate written tasks in their respective disciplines. The study focused on what can be done within a higher education institution in terms of academic writing instruction to develop the literacy abilities required to enable students to cope with the demands of tertiary studies within specific disciplines, as students progress from undergraduate to postgraduate work. Given the varied and specialised nature of academic discourses in different fields of study, a discipline-specific approach to writing instruction was adopted to facilitate students’ familiarity with the conventions of academic and discourse-specific writing, and develop their ability to produce effective and appropriate texts for their courses. A multistage evaluation design was used to measure the potential impact of the writing intervention, there results of which indicate an improvement in students’ academic literacy and writing abilities, as well as their ability to apply these abilities to writing in their subject area.